THE TRANSITION OF I LA GALIGO EPOS INTO A WEBTOON SERIAL FORM AS A LEARNING MEDIA OF BUGINESE CLASSICAL LITERATURE CREATION IN THE DIGITAL ERA - Ade Yustina; Nur Fitri Isneni; Dedi Risaldi (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2019)
Instead of the I La Galigo epos to the Webtoon Series as a LearningMedia for Bugis Classical Literature. The learning process by using media, especially animation media such as webtoon, can provide an easy understanding of students, so as to improve the achievement of student learning outcomes. Integrating local regional wisdom is one way to maintain regional culture. Therefore, this research was conducted to develop learning media in the form of webtoon which aims to increase interest in learning regional languages and as a form of preserving and preserving regional languages in the digital era. This learning media is expected to improve student learning outcomes and interest in learning regional languages. The type of research used in this study is research and development or Research and Development (R & D). This study uses the Recursive, Reflective Design, and Development Model (R2D2) research design.  The data in this study consisted of two categories, namely qualitative data and quantitative data. Qualitative data in the form of responses, suggestions, and criticisms originating from experts and practitioners.  Quantitative data in the form of student responses and scores obtained from tests of the use of instructional media in classical Bugis literature in the form of a webtoon as the transformation of the epic I La Galigo towards SMP Negeri 1 Watansoppeng on effectiveness testing. Analysis of research data is grouped into analysis of qualitative data and quantitative data. Qualitative data analysis is divided into three, namely (1) analysis of preliminary study data, (2) analysis of expert and practitioner test data, and (3) analysis of trial data to prospective users. Qualitative data is analyzed into three stages, namely (1) data management, (2) statistical analysis, and (3) interpretation of results. The results of this study are serial webtoon transformed from the epic I La Galigo as a learning media for classical Bugis literature. Based on expert testing and webtoon practitioners it was declared feasible to use. The use of webtoon as a learning media for classical Bugis literature can foster knowledge and attitudes and increase the interest in learning regional languages in middle school students.